Restoration of peripheral ILC3s by washed microbiota transplantation improves lipid profiles in hyperlipidemia patients - Wei, Yao-Fei; Wang, Yi-Shu; Song, Jia-Yin; Wang, Hao; He, Xing-Xiang; Zhong, Hao-Jie (Frontiers in Immunology, 2025)
BackgroundThe contribution of circulating group 3 innate lymphoid cells (ILC3s) to lipid dysregulation has remained poorly defined, and the mechanisms through which washed microbiota transplantation (WMT) improves lipid metabolism require further clarification.MethodsPeripheral ILC subsets and plasma IL-22 were assessed in hyperlipidemia patients and healthy controls. The lipid-lowering effects of WMT were evaluated in a prospective cohort without lipid-lowering medications. Gut microbial and plasma metabolite profiles before and after WMT were analyzed. A hyperlipidemic mouse model was used to determine whether healthy microbiota promote hepatic ILC3 homing via integrin α4.ResultsHyperlipidemia was characterized by reduced circulating ILC3s, integrin α4+ ILC3s, and plasma IL-22, all of which showed inverse correlations with TC, TG, LDL-C, non-HDL-C, and ApoB. Significant lipid improvements were achieved after WMT, accompanied by increased circulating ILC3s and integrin α4+ ILC3s, paralleling reductions in TC and LDL-C. WMT induced marked remodeling of gut microbiota and plasma metabolites, including taxa and metabolites positively associated with ILC3 restoration and lipid improvement. In hyperlipidemic mice, healthy microbiota transplantation increased hepatic ILC3 and integrin α4+ ILC3 accumulation and improved lipid levels, whereas integrin α4 blockade impaired ILC3 liver homing and attenuated the metabolic benefit.ConclusionHyperlipidemia is associated with depletion of circulating ILC3s and reduced IL-22. Restoration of ILC3 subsets and enhancement of integrin α4–dependent hepatic homing are achieved after WMT, accompanying improvements in lipid metabolism.